2020
DOI: 10.1093/cdn/nzaa053_024
|View full text |Cite
|
Sign up to set email alerts
|

A Participatory Agroecological Intervention Reduces Women’s Risk of Probable Depression Through Improvements in Food Security in Singida, Tanzania

Abstract: Objectives In 2015, depressive disorders led to over 50 million disability-adjusted life years lost globally, with more than 80% occurring in low- and middle-income countries. Depressive disorders are also risk factors of a number of adverse maternal and child health outcomes. To our knowledge, the Singida Nutrition and Agroecology Project (SNAP-Tz), is the first nutrition-sensitive agriculture (NSA) intervention identified to improve women's probable depression (2020). Food security has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Given that children are among the most vulnerable to food insecurity and health, consuming diverse diets could mean that they can gain the necessary nutrients needed for a healthy and active life. In addition to food security, some studies have found that food security achieved through agroecological interventions was associated with positive mental health outcomes [61]. The net effect of these benefits is that households and communities become more resilient to climate change and its impacts.…”
Section: Stimulates Sustainable Food Productionmentioning
confidence: 99%
“…Given that children are among the most vulnerable to food insecurity and health, consuming diverse diets could mean that they can gain the necessary nutrients needed for a healthy and active life. In addition to food security, some studies have found that food security achieved through agroecological interventions was associated with positive mental health outcomes [61]. The net effect of these benefits is that households and communities become more resilient to climate change and its impacts.…”
Section: Stimulates Sustainable Food Productionmentioning
confidence: 99%
“…Most of these factors have been identified through the respective bodies of literature on each, but some new work on the topic has tried to understand common determinants and mechanisms between FSN and mental health through innovative theoretical framing, study design, and more advanced statistical models 28,40 . Recent interventions that at the least measure and at the most include programmatic components of both FSN and mental health have begun to give insight into some of these mechanisms as well 41 .…”
Section: * Pregnant Women and Mothers (Pwm)mentioning
confidence: 99%
“…Low cost mental health interventions, involving nonspecialized or community health providers, have begun to emerge and often show positive impacts for individuals of all ages, including caregivers and children (61,62). FSN programs working to improve gender disadvantage, social cohesion, peer support, decision-making, and agricultural practices may also act on mental health status, which in turn may strengthen engagement with food and nutrition behaviors (63).…”
Section: Interventions and Programmesmentioning
confidence: 99%